(untitled) (Indian Journal of Pure & Applied Physics (IJPAP), 2024)
The increasing presence of toxic gases, particularly acetone, poses significant threats to both the environment and human health. Effective detection of acetone is crucial, necessitating the development of reliable and sensitive sensors. This study explores the use of Nano NaA zeolite as a promising material for acetone sensing, leveraging its excellent adsorption and desorption properties. Comprehensive material characterization is performed using X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis-Differential Thermal Analysis (TG-DTA), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Analysis (EDAX) and Atomic Force Microscopy (AFM). The sensing characteristics of Nano NaA zeolite are rigorously evaluated. The sensor exhibits optimal performance at an operating temperature of 75 °C, with a response time of 88 seconds and a recovery time of 75 seconds. The sensor demonstrates excellent sensitivity at a saturation concentration of 85 ppm. Repeatability tests conducted over three trials confirmes the sensor’s consistent performance, while durability assessments conducted over a 30-day period (with measurements after every 5 days) highlights its long-term stability. Additionally, the study investigates the effect of acetone exposure on optical and dielectric properties of the sensor. This research underscores the potential of Nano NaA zeolite as an effective acetone sensor, offering valuable insights into its optical and dielectric properties. The findings support the development of robust and durable acetone sensors for environmental monitoring and human safety.